On the Design of Fast Wavelet Transform Algorithms With Low Memory Requirements - Oliver, J.; Perez Malumbres, M. (IEEE transactions on circuits and systems for video technology, 2008)
In this paper, a new algorithm to efficiently compute the two-dimensional wavelet transform is presented. This algorithm aims at low memory consumption and reduced complexity, meeting these requirements by means of line-by-line processing. In this proposal, we use recursion to automatically place the order in which the wavelet transform is computed. This way, we solve some synchronization problems that have not been tackled by previous proposals. Furthermore, unlike other similar proposals, our proposal can be straightforwardly implemented from the algorithm description. To this end, a general algorithm is given which is further detailed to allow its implementation with a simple filter bank or using the more efficient lifting scheme. We also include a new fast run-length encoder to be used along with the proposed wavelet transform for fast image compression and reduced memory consumption. When a 5-megapixel image is transformed, experimental results show that the proposed wavelet transform requires 200 times less memory and is five times faster than the regular one. If we consider the whole coding system, numerical results show that it achieves state-of-the-art performance with very low memory requirements and fast execution, becoming an interesting solution for resource-constrained devices such as mobile phones, digital cameras, and PDAs.